Mindfulness – enrichment of the modern lifestyle - Hornborg, Anne-Christine (Journal of spirituality in mental health, 2025)
This article addresses healing practices performed under the umbrella of mindfulness in order to problematize how mindfulness is presented as a means to enrich a modern lifestyle. The discussion considers mindfulness in a contemporary Swedish context, presenting a range of healing practices. A fundamental question asked is if they represent a religious or spiritual practice or just a technique? The discussion also addresses the discursive strategies used by different entrepreneurs in promoting mindfulness. A concern is if mindfulness has become an individual-centered practice aimed at creating a neoliberal persona able to cope with stress and feelings of insufficient creativity?